Um método não destrutivo simples para estimativa de biomassa aérea de macrófitas aquáticas emergentes - Nunes, Laís Samira Correia [UNESP]; Camargo, Antonio Fernando Monteiro [UNESP] (FapUNIFESP (SciELO), 2017)
Aim: Non-destructive methods for estimating aquatic macrophytes biomass may be employed by using indirect measurements, especially in experimental studies, thus enabling the conservation of plant samples. It is possible to estimate macrophyte biomass by developing mathematical equations that relate the plants’ dry mass to their morphological variables. The aim of this study was to evaluate the relationship between different morphological variables and biomass in order to determine which variable is easier to be obtained for the emergent aquatic macrophytes Crinum americanum and Spartina alterniflora. Methods: We obtained the aboveground area and height of individuals of both species, with different sizes and distinct developmental stages. The samples were collected in the Itanhaém River Estuary (SP, Brazil). The plants were dried in a laboratory oven and weighed so as to obtain their dry mass. Simple linear regression analyses were applied to the morphological variables and the individual dry mass to obtain equations. Results: For the both species, the relationship between area and biomass, and the relationship between individual height and biomass presented significant coefficients of determination (p < 0.0001). For the elaboration of models involving the individual height, we used only one morphological measure for each individual, whereas for models involving the individual area it was necessary to obtain more than one hundred morphological measurements per individual. Conclusions: The morphological variables chosen are good attributes for estimating the aboveground biomass of C. americanum and S. alterniflora. Considering the models’ adjustment and the consumed time to obtain the measurements, we conclude that the individual height measurement is better for biomass estimation for both species.
A simple non-destructive method for estimating aboveground biomass of emergent aquatic macrophytes
Keywords: Crinum americanum; Dry mass; Morphological variables; Plant traits; Spartina alterniflora